A comprehensive checklist and host plants of Aphididae (Aphidomorpha: Hemiptera) from Pakistan - Hassan, Muhammad Asghar; Asif, Muhammad; Chakrabarti, Samiran; Amin, Muhammad; Abbas, Zohair; Maryam, Zershina; Iqbal, Zafar; Ali, Muhammad; Qasim, Muhammad; Bashir, Nawaz Haider; Ali, Muhammad Yasir; Xing, Jichun (European Journal of Taxonomy, 2024)
The family Aphididae (Hemiptera) represents one of the most diverse groups of sap-sucking insect pests referred to as aphids or plant-lice, with 366 species reported in Pakistan, associated with wide array of agricultural and horticultural crops, including fruit and forest trees, weeds, grasses, shrubs, and vines. This work aims to provide an updated checklist of aphids and their associated host plants documented across various regions of Pakistan. The checklist consolidates information from various published literature sources, including annotated checklists, regional distribution data, and host plant records from Pakistan. In this study, we present an annotated checklist of 366 aphid species, belonging to 134 genera and 11 subfamilies, associated with a total of 359 host plant species stretched over 84 families in Pakistan.